If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+2(5x-4)+10-3(2x+5)=-4(2x-5)-2(-7x-2)-19
We move all terms to the left:
3x+2(5x-4)+10-3(2x+5)-(-4(2x-5)-2(-7x-2)-19)=0
We multiply parentheses
3x+10x-6x-(-4(2x-5)-2(-7x-2)-19)-8-15+10=0
We calculate terms in parentheses: -(-4(2x-5)-2(-7x-2)-19), so:We add all the numbers together, and all the variables
-4(2x-5)-2(-7x-2)-19
We multiply parentheses
-8x+14x+20+4-19
We add all the numbers together, and all the variables
6x+5
Back to the equation:
-(6x+5)
7x-(6x+5)-13=0
We get rid of parentheses
7x-6x-5-13=0
We add all the numbers together, and all the variables
x-18=0
We move all terms containing x to the left, all other terms to the right
x=18
| 8x-4(x+6)=0 | | -10r=8-9r | | -2j+4=-3j | | 7x-41=6/x | | -4w=-3w-8 | | (12x-5)+125=180 | | -2c+4=-3c | | 4h+2/3=34/3 | | x-34.1862/x-50=0 | | -4w=-3w−8 | | 7p=6p+7 | | -11b+7=4” | | 11x+16x=0 | | 2b/3b+1=-3b/4b+2 | | 7p-3=3(3p-3)-2(5-3p) | | -7x=-10x-26 | | -1=3x+14 | | 155=290-w | | -7(5t-13)=-25 | | -12+30x=0 | | 5x+10=-3x+14 | | 183-w=239 | | 2/3b+1=-3/4b+2 | | 4t-10/2=4t/2-10 | | y/2-6=-5 | | 0.08x=18500 | | 0.08x=18,500 | | -78=-6(u+4) | | 2t-10=4t-5 | | 3(x+3)=2(x—1) | | 8-7w=-27 | | x+(x*5/30)=100 |